Evaluasi Layanan Transportasi Umum Berbasis Aplikasi dan Konvensional menurut Persepsi Pengguna Layanan di Kota Kupang - Bima, Virgilius D.; Seran, Engelbertha Noviani Bria; Seran, Sri Santi L. M. F. (CV. Gio Architect, 2025)
Currently, public transportation is increasingly developing. At first only ordinary public transport was used. However, there are currently many types of online public transportation. This affects people's use of public transportation, both online. The aim of this research is to provide information and knowledge to the public regarding the comparison of Kupang City residents' satisfaction with the use of online public transportation with traditional public transportation using quantitative research methods through questionnaires and processing. information on survey results using SPSS. From the research results obtained, the people of Kupang City feel more satisfied using online transportation compared to conventional public transportation. This is shown by the average satisfaction of people using online public transportation which is higher than traditional public transportation in nine aspects which are the standard for assessing community satisfaction.